Discovery of an optical cocoon tail behind the runaway HD 185806. Issue 1 (12th July 2022) - Spetsieri, Z T; Boumis, P; Chiotellis, A; Akras, S; Derlopa, S; Shetye, S; Meyer, D M-A; Bowman, D M; Gvaramadze, V V
ABSTRACT: Studies on the circumstellar structures around evolved stars provide vital information on the evolution of the parent star and the properties of the local interstellar medium. In this work, we present the discovery and characterization of an optical cocoon tail behind the star HD 185806. The cocoon apex emission is puzzling, as it is detected in the infrared but shows no signal in the optical wavelength. The H α and [O iii ]  fluxes of the nebular structure vary from 2.7 to 8.5 × 10 −12 erg s −1 cm −2 and from 0.9 to 7.0 × 10 −13 erg s −1 cm −2, respectively. Through high-resolution spectroscopy, we derive the spectral type of the star, construct the position–velocity diagrams of the cocoon tail for the H α, [O iii ], and [N ii ] emission lines, and determine its velocity in the range of −100–40 km s −1 . Furthermore, we use SED fitting and mesa evolutionary models adopting a distance of 900 pc, and classify HD 185806 as a 1.3 M⊙ star, in the transition phase between the RGB and early AGB stages. Finally, we study the morpho-kinematic structure of the cocoon tail using the astronomical software SHAPE. An ellipsoidal structure, with an inclination of ∼19° with respect to the plane of sky is found to better reproduce the observed cocoon tail of HD 185806.